2020
DOI: 10.1111/boc.202000031
|View full text |Cite
|
Sign up to set email alerts
|

Brefeldin A inhibits clathrin‐dependent endocytosis and ion transport in Chara internodal cells

Abstract: Background. The Characeae are multicellular green algae, which are closely related to higher plants. Their internodal cells are a convenient model to study membrane transport and organelle interactions. Results. In this study, we report on the effect of brefeldin A (BFA), an inhibitor of vesicle trafficking, on internodal cells of Chara australis. BFA induced the commonly observed agglomeration of Golgi bodies and trans Golgi network into 'brefeldin compartments' at concentrations between 6 and 500 μM and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…JTE013 (8 μM) enhanced both Wnt3a and Wnt5a/b protein levels in BMSCs cultured in osteogenic media compared with BMSCs treated with DMSO from day 3 to day 9 ( Figure 6 M). To further determine whether Wnt3a and Wnt5a/b protein expressions were associated with vesicle trafficking, murine BMSCs were treated with brefeldin A (BFA, an inhibitor of protein trafficking from ER to Golgi) [ 46 , 47 ] or DMSO and cultured in osteogenic media for 6 days. Treatment with BFA suppressed both Wnt3a and Wnt5a/b protein expressions in BMSCs compared with DMSO treatment ( Figure 6 N).…”
Section: Resultsmentioning
confidence: 99%
“…JTE013 (8 μM) enhanced both Wnt3a and Wnt5a/b protein levels in BMSCs cultured in osteogenic media compared with BMSCs treated with DMSO from day 3 to day 9 ( Figure 6 M). To further determine whether Wnt3a and Wnt5a/b protein expressions were associated with vesicle trafficking, murine BMSCs were treated with brefeldin A (BFA, an inhibitor of protein trafficking from ER to Golgi) [ 46 , 47 ] or DMSO and cultured in osteogenic media for 6 days. Treatment with BFA suppressed both Wnt3a and Wnt5a/b protein expressions in BMSCs compared with DMSO treatment ( Figure 6 N).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cells treated with chlorpromazine (an inhibitor of clathrin-mediated endocytosis), colchicine (an inhibitor of microtubule formation and macropinocytosis), and brefeldin A (an inhibitor of protein transport from the endoplasmic reticulum to the Golgi apparatus) showed a 36%, 39%, and 31% decrease in cellular uptake, respectively as reflected in the decrease in fluorescence signals. The cellular uptake of rhApoE/Cou-6/Aβ-CN-PMs was partially dependent on clathrin-mediated endocytosis, macropinocytosis, and the Golgi apparatus [ 41 43 ]. Sodium azide (NaN 3 ) is used to inhibit energy-dependent endocytosis by disrupting ATP production.…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed that BFA inhibited the heat-induced nuclear PA elevation and also nuclear translocation of GAPC. While BFA has been used to block the exocytosis by preventing COP-coated vesicle transport from the ER to Golgi membranes, evidence suggests that it also suppresses the retrograde trafficking in animals, plants, and green algae (Grebe et al, 2003; Jelínková et al, 2015; Zhang et al, 2019b; Foissner et al, 2020). Thus, the data support the model that PA mediates the stress-induced nuclear translocation of GAPC via binding of GAPC and then trafficking of the PA-GAPC-containing vesicles to the nucleus (Figure 8).…”
Section: Discussionmentioning
confidence: 99%